Variability of gross tumour volume delineation: MRI and CT based tumour and lymph node delineation for lung radiotherapy. (February 2022) - Kumar, Shivani; Holloway, Lois; Boxer, Miriam; Yap, Mei Ling; Chlap, Phillip; Moses, Daniel; Vinod, Shalini
Highlights: Inclusion of anatomical MRI does not increase inter-observer variability. T2 weighted HASTE sequence ideal for lung primary and nodal GTV delineation. GTV delineation guide is essential to maximise benefit of MRI guided radiotherapy. MRI can be a comprehensive imaging modality to guide GTV delineation for lung radiotherapy delineation. Abstract: Purpose: To compare gross tumour volume (GTV) delineation of lung cancer on magnetic resonance imaging (MRI) and positron emission tomography (PET) versus computed tomography (CT) and PET. Methods: Three experienced thoracic radiation oncologists delineated GTVs on twenty-six patients with lung cancer, based on CT registered to PET, T2-weighted MRI registered to PET and T1-weighted MRI registered with PET. All observers underwent education on reviewing T1 and T2 images along with guidance on window and level setup. Interobserver and intermodality variation was performed based on dice similarity coefficient (DSC), Hausdorff distance (HD), and average Hausdorff distance (AvgHD) metrics. To compute interobserver variability (IOV) a simultaneous truth and performance level estimation (STAPLE) volume for each image modality was used as reference volume. For intermodality analysis, each observers CT based primary and nodal GTV was used as reference volume. Results: A mean DSC of 0.9 across all observers for primary GTV (GTVp) and a DSC of >0.7 for nodal GTV (GTVn) was demonstrated for IOV. Mean T2 and T1 GTVp and GTVn were smaller than CT GTVp and GTVn but the difference in volume between modalities was not statistically significant. Significant difference ( p < 0.01) for GTVp and GTVn was found between T2 and T1 GTVp and GTVn compared to CT GTVp and GTVn based on DSC metrics. Large variation in volume similarity was noted based on HD of up-to 5.4 cm for observer volumes compared to STAPLE volume. Conclusion: Interobserver variability in GTV delineation was similar for MRI and PET versus CT and PET. The significant difference between MRI compared to CT delineated volumes needs to be further explored.